Suppression Colitis and Colitis-Associated Colon Cancer by Anti-S100a9 Antibody in Mice - Zhang, Xuemei; Wei, Lingyu; Wang, Jing; Qin, Zailong; Wang, Jia; Lu, Yuanjun; Zheng, Xiang; Peng, Qiu; Ye, Qiurong; Ai, Feiyan; Liu, Peishan; Wang, Siwen; et al. (Frontiers in Immunology, 2017)
The association between chronic inflammation and cancer has long been recognized. The inflammatory bowel disease ulcerative colitis frequently progress to colon cancer, however, the underlying mechanism is still unclear. S100a9 has been emerged as an important pro-inflammatory mediator in acute and chronic inflammation, and the aberrant expression of S100a9 also contributes to tumorigenic processes such as cell proliferation, angiogenesis, metastasis, and immune evasion. We previously revealed that S100a8 and S100a9 are highly activated and play an important role in the process of colitis-associated carcinogenesis, which suggests an attractive therapeutic target for ulcerative colitis and related colon cancer. Here, we report that administration of a neutralizing anti-S100a9 antibody significantly ameliorated dextran sulfate sodium (DSS)-induced colitis and accompanied by diminished cellular infiltrate of innate immunity cells (macrophages, neutrophils, and dendritic cells) and production of pro-inflammatory cytokines (Tnfα, Il1β, Ifnγ, Il6, Il17a, Il23a, Il4 and Il12a). The protective effect of anti-S100a9 antibody treatment was also observed in Azoxymethane (AOM)/DSS-induced colitis-associated cancer (CAC) mouse model. The inflammatory response, tumor cell proliferation and immune cells infiltration in the colon tissues were suppressed by anti-S100a9 antibody. Gene expression profiling showed that key pathways known to be involved in CAC development, such as Wnt signaling pathway, PI3K-Akt signaling pathway, cytokine-cytokine receptor interaction, and ECM-receptor interaction pathway, were suppressed after treatment with anti-S100a9 antibody in CAC mice. In view of the protective effect of neutralizing anti-S100a9 antibody against DSS-induced colitis and AOM/DSS-induced CAC in mouse model, this study suggests that anti-S100a9 antibody may provide a novel therapeutic approach to treat ulcerative colitis and may decrease the risk for developing CAC.